Integration of Local Wisdom and Islamic Teachings in Reducing Domestic Violence in Muslim Communities - Mubarok, Abdul (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2024)
Domestic violence remains a significant issue in many societies, including Muslim communities, despite religious teachings promoting peace and family harmony. This study explores the integration of local wisdom and Islamic teachings as a strategy to reduce domestic violence in Muslim communities. Using a qualitative approach, this research employs literature review and library research methods to analyze the alignment of Islamic principles with local cultural practices that emphasize respect, kindness, and mutual understanding within the family. The study reviews Islamic texts, such as the Qur’an and Hadith, alongside indigenous cultural values that promote non-violence and social harmony. It highlights the potential for synergizing these two sources to create a comprehensive framework that can guide community interventions, educational programs, and policy initiatives. The findings suggest that integrating Islamic teachings on justice, compassion, and the sanctity of family life with local wisdom, such as conflict resolution strategies and the role of elders in mediation, can be effective in preventing and addressing domestic violence. By fostering an environment where both spiritual and cultural values are respected, Muslim communities can build stronger, non-violent family structures. The research emphasizes the importance of community-based approaches in creating sustainable change and highlights the need for further studies on the practical application of these integrated values in real-world settings.